2022
DOI: 10.1177/14644207221110483
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption of foam-filled corrugated core sandwich panels under quasi-static loading

Abstract: The present paper tries to introduce the effect of foam-filled on a type of trapezoidal corrugated core and their structures derived from the related previous studies. The main purpose of this work is to present a novel geometry of trapezoidal cores, and their configurations are inspired by the earlier works. These absorbers have been proposed to raise the specific energy absorption (SEA) while declining the initial peak crushing force. Therefore, five corrugated core sandwich panels have been tested under qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…There are various types of conventional core materials, such as foam core, corrugated core, honeycomb core, truss/lattice core, and hybrid core that amalgamates foam with another type of core structure. The selection of the core material hinges upon the specific application requirements and loading characteristics [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of conventional core materials, such as foam core, corrugated core, honeycomb core, truss/lattice core, and hybrid core that amalgamates foam with another type of core structure. The selection of the core material hinges upon the specific application requirements and loading characteristics [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of their study demonstrated that the influence of geometric parameters on effective performance played a crucial role in enhancing the mechanical properties of corrugated lattice-core sandwich plates. Taghipoor et al 8 obtained and analyzed the energy absorption of foam-filled corrugated core sandwich panels under quasi-static loading and their comparative findings indicate that the specific energy absorption rate of bi-core sandwich panels that have not been filled with foam surpasses that of the single trapezoidal core sandwich panels. Subani et al 9 investigated the static analysis of honeycomb sandwich structures using numerical methods and analyzed the sandwich structures under different boundary conditions and loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al 18 obtained through the quasi-static experiment that the smaller unit cell radius height ratio and length height ratio can produce more obvious negative Poisson's ratio effects. Hossein Taghipoor et al [19][20][21][22] have conducted many detailed studies on sandwich beams with expanded metal sheets as cores. These studies analyzed the impact of various parameters (such as the influence of the cell orientation and size of the cell, 21 the core layer number and thickness of the substrates, 20 and the direction of the lattice sheets) 19 on structural performance.…”
Section: Introductionmentioning
confidence: 99%